Efeito do extrato das raízes de Bredemeyera floribunda Willd sobre a ação local do veneno de Bothrops jararacussu em camundongos - Alves, Natacha Teresa Queiroz (2013)
Snakebites are an important public health burden. In Brazil, most of these accidents are caused by snakes of the Bothrops genus that can lead to development of local tissue damage, including edema and hemorrhaging. Traditional antivenom therapy acts in the neutralization of systemic effects, but it has limited effectiveness of neutralizing the local effects. The antivenom activity was evaluated of aqueous extract of Bredemeyera floribunda (Bfe) through inhibition of phospholipase, proteolytic, edematogenic, hemorrhagic, necrotizing and myotoxic actions promoted by the total Bothrops jararacussu venon (Bjuv) in mice. The acute toxicity and the viability cell of the Bfe in RAW 264.7 cells were determined too. The BfE showed to be nontoxic in mice and it showing LD50 greater than the test dose (2000 mg / kg). The Bfe increased cell viability in RAW 264.7 cells. The phospholipase and proteolytic activities induced vBju were inhibited in vitro by EBF in 1:1, 1:2 and 1:3 ratios. 1:2 (Bjuv /Bfe; w/w). The Bfe also inhibited significantly edema induced by Bjuv, with a reduction of the peak oedematogenic in the venom and carrageenan groups, mainly in the group pretreated i.p. The Bfe decreased considerably hemorrhagic, necrotizing and myotoxic actions by Bjuv. Compounds isolated from plants popularly used to treat snake poisoning show good alternative to complement the antivenom treatment. Constituents of the Bfe may act by binding to Bjuv components as phospholipase A2 and their homologues and matalloproteases too, partly blocking the action of these proteins, reducing edema and phospholipasic activities, but also hemorrhaging and proteolytic activities. So there is real antiophidic activity of the extract, making necessary to study it with isolated components of the Bfe and Bjuv to achieve better evidences of the effects and possible mechanisms.